Modulation of sleep behavior in zebrafish larvae by pharmacological targeting of the orexin receptor - Pardon, Marie; Claes, Pieter; Druwé, Sarah; Martini, Murielle; Siekierska, Aleksandra; Menet, Christel; de Witte, Peter A. M.; Copmans, Daniëlle (Frontiers in Pharmacology, 2022)
New pharmacological approaches that target orexin receptors (OXRs) are being developed to treat sleep disorders such as insomnia and narcolepsy, with fewer side effects than existing treatments. Orexins are neuropeptides that exert excitatory effects on postsynaptic neurons via the OXRs, and are important in regulating sleep/wake states. To date, there are three FDA-approved dual orexin receptor antagonists for the treatment of insomnia, and several small molecule oral OX2R (OXR type 2) agonists are in the pipeline for addressing the orexin deficiency in narcolepsy. To find new hypnotics and psychostimulants, rodents have been the model of choice, but they are costly and have substantially different sleep patterns to humans. As an alternative model, zebrafish larvae that like humans are diurnal and show peak daytime activity and rest at night offer several potential advantages including the ability for high throughput screening. To pharmacologically validate the use of a zebrafish model in the discovery of new compounds, we aimed in this study to evaluate the functionality of a set of known small molecule OX2R agonists and antagonists on human and zebrafish OXRs and to probe their effects on the behavior of zebrafish larvae. To this end, we developed an in vitro IP-One Homogeneous Time Resolved Fluorescence (HTRF) immunoassay, and in vivo locomotor assays that record the locomotor activity of zebrafish larvae under physiological light conditions as well as under dark-light triggers. We demonstrate that the functional IP-One test is a good predictor of biological activity in vivo. Moreover, the behavioral data show that a high-throughput assay that records the locomotor activity of zebrafish throughout the evening, night and morning is able to distinguish between OXR agonists and antagonists active on the zebrafish OXR. Conversely, a locomotor assay with alternating 30 min dark-light transitions throughout the day is not able to distinguish between the two sets of compounds, indicating the importance of circadian rhythm to their pharmacological activity. Overall, the results show that a functional IP-one test in combination with a behavioral assay using zebrafish is well-suited as a discovery platform to find novel compounds that target OXRs for the treatment of sleep disorders.